2012
DOI: 10.1371/journal.pgen.1003102
|View full text |Cite|
|
Sign up to set email alerts
|

Selective Pressure Causes an RNA Virus to Trade Reproductive Fitness for Increased Structural and Thermal Stability of a Viral Enzyme

Abstract: The modulation of fitness by single mutational substitutions during environmental change is the most fundamental consequence of natural selection. The antagonistic tradeoffs of pleiotropic mutations that can be selected under changing environments therefore lie at the foundation of evolutionary biology. However, the molecular basis of fitness tradeoffs is rarely determined in terms of how these pleiotropic mutations affect protein structure. Here we use an interdisciplinary approach to study how antagonistic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 49 publications
(54 reference statements)
1
71
1
Order By: Relevance
“…Studies exposing bacteriophages uX174 and ID11, similar genotypes to our ID8 ancestor, to moderate temperatures (37°and 41.5°) in E. coli hosts resulted in changes in viral capsid proteins that were likely stabilizing and came with a cost of growth rate Lee et al 2011). One study found a single antagonistically pleiotropic mutation in bacteriophage u6 that resulted in a tradeoff between growth rate and capsid stability after exposing evolving populations to a heat-shock selection (Dessau et al 2012). Our results differ from these studies because our heat-shock temperature may have exerted a stronger selection pressure on capsid stability (80°vs.…”
Section: Strong Selection Reveals Synergistic Pleiotropymentioning
confidence: 99%
“…Studies exposing bacteriophages uX174 and ID11, similar genotypes to our ID8 ancestor, to moderate temperatures (37°and 41.5°) in E. coli hosts resulted in changes in viral capsid proteins that were likely stabilizing and came with a cost of growth rate Lee et al 2011). One study found a single antagonistically pleiotropic mutation in bacteriophage u6 that resulted in a tradeoff between growth rate and capsid stability after exposing evolving populations to a heat-shock selection (Dessau et al 2012). Our results differ from these studies because our heat-shock temperature may have exerted a stronger selection pressure on capsid stability (80°vs.…”
Section: Strong Selection Reveals Synergistic Pleiotropymentioning
confidence: 99%
“…For example, in longitudinal experiments that challenged phage T7 with urea 13 and phages ϕ6 and ϕX174 with heat, 14,15 the evolved strains were found to possess increased resistance to their respective stressors but also decreased fecundity. In a study that assessed numerous physical and physiological properties of 16 coliphages (phages that infect Escherichia coli) for covariance with their rates of spontaneous decay, Da Paepe and Taddei found the coliphages' decay rates to be positively correlated with their replication rates.…”
Section: Persistencementioning
confidence: 99%
“…Our results show that joint consideration of different life history traits is necessary for understanding virus evolution, as shown with experimental populations of phages or wild populations of avian influenza virus (56,71,72). The consequence of the reported pleiotropic effects of resistance-breaking mutations for the evolution of resistance-breaking is a complex one.…”
Section: Discussionmentioning
confidence: 72%
“…This result is consistent with previous ones, as data on the within-host fitness of some of the CP mutants analyzed here, reported by MorenoPérez et al (25), showed no correlation with our present stability data in different susceptible hosts (not shown). To our knowledge, the relationship between survival and multiplication has not been studied for other plant viruses, but studies with bacterial or animal-infecting viruses have demonstrated that such a trade-off is not general across systems (55)(56)(57)(58)(67)(68)(69)(70)(71)(72). Trade-offs between survival and reproduction, predicted by the life history theory, need not apply for viruses, because there is no obvious mechanistic reason to expect them due to the differences between the extracellular and intracellular environments where survival and reproduction, respectively, occur, as pointed out by Goldhill and Turner (19).…”
Section: Discussionmentioning
confidence: 99%